1992
DOI: 10.1113/expphysiol.1992.sp003646
|View full text |Cite
|
Sign up to set email alerts
|

Differences between sheep excreting sodium predominantly in their urine or in their faeces: the effect of changes in sodium intake

Abstract: SUMMARYSheep receiving a total of about 31 mmol day-1 (0-5 mmol kg-') of sodium were classified according to the predominant route of sodium excretion; urinary (U) or faecal (F). U sheep had a greater water turnover than F sheep; their intake was 41 % higher and they produced 133 % more urine but there was little difference in faecal water loss. Most faecal sodium was readily exchangeable with water in both groups. When sodium intake was reduced by 80 % (to 6 mmol day-1; 0'1 mmol kg-'), the reduction in total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The U sheep excreted 41 % of their sodium in faeces, whereas F sheep excreted 69 % in faeces (compared with 38 and 86 % when these sheep were tested previously; Michell & Moss, 1992b). As before, the U slheep had a higher water turnover, with both water intake and urine output significantly exceeding those of F sheep (P < 0 05; Table 1).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The U sheep excreted 41 % of their sodium in faeces, whereas F sheep excreted 69 % in faeces (compared with 38 and 86 % when these sheep were tested previously; Michell & Moss, 1992b). As before, the U slheep had a higher water turnover, with both water intake and urine output significantly exceeding those of F sheep (P < 0 05; Table 1).…”
Section: Resultssupporting
confidence: 56%
“…Two groups of six Scottish Blackface ewes, which had already been classified as U or F excretors of sodium (Michell & Moss, 1992b), were re-accustomed to metabolism cages and diets of specified sodium contcnt. The basal diet comprised 0 5 kg oats, 0-3 kg straw, 0.2 kg bran and a mineral-vitamin supplement (31 g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, urine osmolality increased with aging in the basal state and yet urine sodium decreased. While the reasons are not fully understood, studies in sheep showed that sometimes daily sodium output is regulated in these animals by increasing fecal sodium excretion with a greater increase in urinary potassium with phosphate and urea excretion also suggested to be greater (21). Therefore, it is possible that the increase in urine osmolality with a lower sodium excretion in our study reflects an increase in other ions and electrolytes.…”
Section: Discussionmentioning
confidence: 46%
“…However, given the degree of disparity in sodium excretion between the groups, which one would predict would cause marked increases in extracellular fluid volume and arterial pressure, it is unlikely to simply reflect sodium retention. It is possible that reabsorption via the gut is altered or influenced by circadian rhythm in the uni-x animals (37), more sodium is being sequestered in the sheep rumen, or fecal sodium excretion (19) is greater in the uni-x animals. It is also possible that the diurnal regulation of renal function is altered in the uni-x animals.…”
Section: Discussionmentioning
confidence: 98%